Informação estratégica: indicadores educacionais e os órgãos de fomento - Alves, Paula Regina de Moura França (2017)
In the educational context of accountability policies, it is necessary for scholar actors can reflect about educational indicators. In this sense, the appropriation of educational indicators by school teams can contribute to educational improvement in its broad sense, since from them; it is possible to monitor the results achieved and the obstacles to be overcome; as well as appealing to the funding agencies of education. The purpose of this search was to study the educational indicators and their implications in obtaining resources from development agencies. The development agencies monitor their investments through indicators that work like a compass, a fact that requires a broad understanding of them from those involved in the process. In methodological terms, it is a research delimited by qualitative approach, supported by descriptive typology. For goals achieve, the documentary research was used, method, and for their analysis, the content analysis technique. With research development, it was verified that there are many resources destined for education, however it necessary that scholar teams have knowledge about capturing them; as well as was evident that the work with educational indicators needs to be expanded among the teams as a way to enable the necessary improvements in contemporary education. As a final result, it was obtained a framework construction, in order to contribute to the scholar management to capture the necessary resources for educational quality improvement.